MOTIVASI KERJA KARYAWAN DI DINAS PARIWISATA PEMUDA DAN OLAHRAGA KABUPATEN KEPULAUAN MERANTI - Razman, Bakhtiar; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
One of the important assets owned by the organization can not be separated from the performance of employees. To obtain good performance, it is necessary to improve employee motivation. In developing the organization, people often focus on how to develop the business while the development of human resources is still less attention. A good leader will certainly create a comfortable environment and motivate employees with the aim to work morale to work and provide maximum performance. Work motivation is an important factor to obtain good performance.This study was conducted with the aim to determine what factors affect employee motivation and what factors are dominant influence employee motivation in Tourism Office of Youth and Sports District of Meranti IslandsThe method used in this study is a quantitative method using statistical formula to help analyze data obtained from the field. The data in this study was obtained by spreading questionnaires on 29 respondents who became samples and then processed to get the results. The results of this study concluded that: 1) factors that affect the motivation of work is the factor of satisfaction and maintenance factor. 2) the most dominant factor affecting the work motivation of employees at the Department of Tourism Youth and Sports District of Meranti Islands is a maintenance factor.Keywords : Work Motivation